Ekspresi gen litik virus Epstein-Barr: manfaatnya untuk penegakan diagnosis karsinoma nasofaring - Daniel Joko Wahyono; Bambang Hermani; Purnomo Soeharso (Oto Rhino Laryngologica Indonesiana, 2010)
Background: Nasopharyngeal carcinoma (NPC) is endemic in certain geographic regions, such asSoutheast Asia, and is associated with several environmental and genetic factors. Undifferentiated NPCis consistent with Epstein-Barr virus (EBV) infection. NPC is the most common ENT tumor in Indonesiawith high prevalence among native populations and yearly overall incidence estimated 6.2 per 100.000 population. Purpose: To explain the advantage of EBV immediate-early gene expression analysis indetermining of NPC diagnosis and management of NPC.Review: Replication of EBV implies to twocellular reactions, i.e. latentcy and lytic cycle expression of EBV lytic genes which consists of three lyticphases, i.e. immediate-early, early and late phase. Expression of immediate-early genes BZLF1 andBRLF1 are needed to induct of early and late genes, so both genes are known as transactivator genes.BALF1, an early lytic gene, expresses some protein regulating EBV replication in NPC. Expression of BCLF1, a late lytic gene, is essential for EBV replication, particularly in the forming of virion structure inNPC. Switching from latent to lytic cycle in tumor cells can happened spontaneously, particularly whenthe viral immediate early genes are induced via signal transduction after initial activation by anti-IgG,TGF-ß and CD4+. In NPC, the induction of EBV lytic cycle by cisplatin and irradiation gamma leads tothe increasing expression of BRLF1 and BZLF1 which have a correlation with the increasing of tumorprogression. RT-PCR technique is a very useful for detecting mRNA BRLF1 and BZLF1 gene expressionat the site of primary tumor, while real-time RT-PCR technique is used to measure the mRNA level ofthose genes.Conclusion: Expression of EBV immediate-early lytic gene in the biopsy of NPC primarytumour provides a basic clinical information for NPC diagnosis and therapy more accurately. Key words: expression EBV lytic gene, nasopharyngeal carcinoma, NPC diagnosis. Abstrak : Latar belakang: Karsinoma nasofaring (KNF) bersifat endemik secara geografis (di Asia Tenggara)dan berasosiasi dengan beragam faktor lingkungan dan genetik. KNF tidak berdiferensiasi konsistendengan adanya infeksi virus Epstein-Barr (VEB). Prevalensi KNF pada populasi Indonesia cukup tinggisebesar 6,2/100.000 penduduk per tahun. Tujuan:Menjelaskan kegunaan analisis ekspresi gen litikimmediate-early VEB untuk menegakkan diagnosis KNF dan meningkatkan efisiensi dalam penangananKNF. Tinjauan Pustaka: Replikasi VEB pada epitel nasofaring berimplikasi pada dua reaksi seluler,yaitu siklus laten dan litik VEB. Ekspresi gen litik VEB terdiri dari tiga fase, yaitu immediate-early,early dan late.Ekspresi gen immediate-early BZLF1 dan BRLF1 diperlukan untuk menginduksi genlitik fase early dan late, sehingga kedua gen tersebut dikenal sebagai gen transaktivator. Gen faseearlylitik BALF1 mengekspresikan protein replikasi pada KNF. Ekspresi gen fase late BCLF1 berperanpenting untuk replikasi VEB pada KNF, terutama untuk membentuk struktur virion. Perubahan sikluslaten menjadi siklus litik pada sel tumor dapat terjadi secara spontan, terutama melalui transduksi sinyalsetelah aktivasi oleh anti-IgG, TGF-ß dan CD4. Pada KNF, induksi siklus litik VEB dengan cisplatindan radiasi sinar γ menyebabkan peningkatan ekspresi gen BRLF1 dan BZLF1 yang berkorelasi denganpeningkatan progresivitas tumor. Teknik RT-PCR akan sangat berguna untuk mendeteksi ekspresi mRNAgen BRLF1 dan BZLF1 VEB pada lokasi tumor primer, sedangkan teknik real time RT-PCR digunakanuntuk mengukur kuantitas mRNA gen tersebut. Kesimpulan: Ekspresi gen litik immediate-early VEBpada biopsi tumor KNF memberikan informasi klinis dasar yang lebih akurat untuk diagnosis dan terapiKNF.+Kata kunci: ekspresi gen litik VEB, karsinoma nasofaring, diagnosis KNF.